Challenges in the implementation of project management in developing countries: the case of Sultanate of Oman - al Muqeemi, Hilal Mohammed Khalifa; Said, Ilias; Kadir Pakir, Abd Hamid; Osman, Omar (2008)

(untitled)
The main objective of a construction project is to complete a project successfully; that is to complete on time, within budget and standard quality as specified. The objective of this paper is to explore the limitation and difficulties encountered by project manager in the implementation of the project management concept in the government project in the Sultanate of Oman. This study uses survey as the medium of date collection. The questionnaires were distributed to respondents that are directly involved in the project life cycle; from feasibility stage, design, procurement, construction phases until the completion of projects. The results of the survey found obstacles associated with the implementation of project management concept in the government projects. These include the identification of causes of delay, and variation orders. The results of this study revealed that the lack clients’ awareness on the project management concept gave an impact on the implementation of project management concept in government projects. This study further found that variation orders and additional works are significant causes of delay in projects; especially in government projects. This paper also suggests recommendation to overcome these problems and insights for future research.